Rapid identification and isolation of neuraminidase inhibitors from mockstrawberry (Duchesnea indica Andr.) based on ligand fishing combined with HR-ESI-Q-TOF-MS - Sifan Luo; Linbo Guo; Caimin Sheng; Yumei Zhao; Ling Chen; Chufang Li; Zhengjin Jiang; Haiyan Tian (Elsevier, 2020)
Neuraminidase inhibitors (NAIs) are the mainstay antiviral drugs against influenza infection. In this study, a ligand fishing protocol was developed to screen NAIs using neuraminidase immobilized magnetic beads (NA-MB). After verifying the feasibility of NA-MB with an artificial mixture including NA inhibitors and non-inhibitors, the developed ligand fishing protocol was applied to screen NAIs from the crude extracts of Duchesnea indica Andr. Twenty-four NA binding compounds were identified from the normal butanol (n-BuOH) extract of D. indica as potential NAIs by high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (HPLC-Q-TOF-MS) assisted with Compound Structure Identification (CSI):FingerID, including 12 ellagitannins, 4 brevifolin derivatives, 3 ellagic acid derivatives, and 4 flavonoids. Among them, 9 compounds were isolated and tested for in vitro NA inhibitory activities against NA from Clostridium perfringens, and from oseltamivir sensitive and resistant influenza A virus strains. The results indicate that compound B23 has the NA inhibitory activities in both the oseltamivir sensitive and resistant viral NA, with half maximal inhibitory concentration (IC50) values of 197.9 and 125.4 μmol/L, respectively. Moreover, B23 can obviously reduce the replication of oseltamivir sensitive and resistant viruses in Madin-Darby canine kidney (MDCK) cells at the concentrations of 40 and 200 μmol/L.